High-performance NO2 gas sensor based on reduced graphene oxide/ZrO2 hybrids - FRAIH, Ali Jabbar; NAEEMA, Nadia; ABBAS, Fatima Fadhil (Journal of Metals, Materials and Minerals, 2024)
The increasing concern over environmental pollution, particularly from nitrogen dioxide (NO2) emissions, necessitates the development of efficient NO2 detection sensors. This study introduces reduced graphene oxide (rGO)/ZrO2 hybrids for enhanced NO2 gas sensing. Utilizing a modified Hummer’s method, graphene oxide (GO) flakes were synthesized and subsequently sputtered with 10 nm ZrO2 film, followed by thermal annealing to produce rGO/ZrO2 hybrids. The hybrids were characterized using various techniques including SEM, TEM, AFM, Raman spectroscopy, and XRD, confirming successful synthesis and reduction of GO, as well as the formation of ZrO2 nanoparticles. Gas sensing tests revealed superior sensitivity to NO2 in the hybrids due to efficient electron transfer between rGO and ZrO2, resulting in increased hole concentration in rGO and enhanced conductivity. The cyclic performance of the hybrids showed stable response and recovery to NO2, while selectivity tests demonstrated high sensitivity to NO2 over other gases including NH3, ethanol, and oxygen. This study highlights the potential of rGO/ZrO2 hybrids as high-performance NO2 gas sensors, offering promising prospects for environmental monitoring and public health protection.